Successful experience of tofacitinib treatment in patients with Fibrodysplasia Ossificans Progressiva - Irina P. Nikishina; Svetlana V. Arsenyeva; Valeria G. Matkava; Alia N. Arefieva; Mariya I. Kaleda; Alexandr V. Smirnov; Leonid M. Blank; Mikhail M. Kostik (BMC, 2023)
Abstract Fibrodysplasia ossificans progressive (FOP) is an ultra-rare genetic disorder that is caused by a mutation in the ACVR1 gene and provokes severe heterotopic ossification. Since flares of the disease are associated with inflammation, it is assumed that JAK inhibitors can control active FOP due to blocking multiple signaling pathways.